An improved assembly homogenization approach for plate-type research reactor. (November 2015) - Ma, Jimin; Wang, Guanbo; Yuan, Shu; Huang, Hongwen; Qian, Dazhi
Highlights: An improved assembly homogenization approach is developed for plate-type research reactor. The approach includes direct assembly calculation and SPH equivalence method. The assembly environmental effect is considered with multi-assembly calculations and assembly classification. The control rod worth can be calculated accurately by the improved approach. Abstract: We have developed an improved assembly homogenization approach for plate-type research reactor. Compared with the conventional cell and assembly homogenization way, three advanced homogenization methods are used in our improved approach, including the direct single and multi-assembly calculations, treatment of the assembly environmental effect by multi-assembly calculations and assembly classification, and the superhomogenization (SPH) method. The approach is carried out with DRAGON v4 code. The neutronic analysis for fresh fueled core of JRR-3M with UAl x –Al dispersion type fuel is carried out by diffusion code CITATION with 3-group homogenized cross sections which are generated by the improved approach. Results by Monte Carlo code are taken as references, and results by the conventional three-step method are given for comparison purposes. The calculation results show that the improved assembly homogenization approach is effective to improve the accuracy of keff eigenvalue, control rod worth and neutron flux distributions for whole core calculations. Especially, the control rod worth can be calculated accurately by the improved approach.